A study on using wide-flange section web under out-of-plane flexure for passive energy dissipation. - Benavent-Climent, Amadeo (Earthquake engineering & structural dynamics.)
It is not common to purposely subject the web of wide-flange or I-sections to out-of-plane bending. However, yielding the web under this loading condition can be a stable source of energy dissipation as the transition at the corner from the web to the flanges is smooth and weld-free; this prevents stress concentrations causing premature failure and eliminates uncertainties and imperfections associated with welding. Further, short segments of wide-flange or I-sections constitute a simple and inexpensive energy dissipating device as minimum manufacturing is required and leftovers not useful for other structural purposes can be re-utilized. This paper proposes a new type of seismic damper in the form of braces based on yielding the web of short length segments of wide-flange or I-shaped steel sections under out-of-plane bending. The hysteretic behavior and ultimate energy dissipation capacity is investigated via component tests under cyclic loads. The experimental results indicate that the damping device has stable restoring force characteristics and a high energy dissipation capacity. Based on these results, a simple hysteretic model for predicting the load?displacement curve of the seismic damper is proposed, along with a procedure for predicting its ultimate energy dissipation capacity and anticipating its failure under arbitrarily applied cyclic loads. The procedure considers the influence of the loading path on the ultimate energy dissipation capacity. Finally, shaking table tests on half-scale structures are conducted to further verify the feasibility and effectiveness of the new damper, and to assess the accuracy of the hysteretic model and the procedure for predicting its failure.